Flipping the Classroom in Political Science: Student Achievement and Perceptions - Betti, Andrea; García Domonte, Aurora; Biderbost, Pablo (Revista de Ciencia Política, 2020)
The flipped-classroom method is acquiring importance as a pedagogical technique to improve the learning performance of students. So far, most studies have examined the possible applications of the flipped-classroom method in the natural sciences realm, with most analyses certifying its positive impact. It has been applied much less frequently in the realm of the social sciences, particularly in political science. Our project aims to generate data about active learning in political science by conducting an experiment in a class entitled “Regional Studies: Latin America.” Using quantitative analysis, we study academic performance in a flipped class, and through qualitative analysis, we explore student perceptions about the flipped classroom and other active-learning techniques.